Intubating the newborn - Littleford, J. A.; American Academy of Pediatrics (Elk Grove Village, IL : American Academy of Pediatrics, 1996)
(Producer) This video is designed for practitioners who assist with, teach, and perform tracheal intubation. Relevant anatomy is reviewed. The procedural sequence is described in detail, using both animation and demonstration on a manikin. Emphasis is placed on pre-clinical instruction.
Videocassette is available at Koleksi Media Perpustakaan HUKM
Funded in part by The Program Development Fund, University of Manitoba and by Laerdal Medical Corporation
Keywords: Resuscitation -- methods -- infant, newborn; Intubation, Intratracheal -- methods -- infant, newborn; Asphyxia Neonatorum -- therapy